FACTORS AFFECTING MILK PRICE IN GETASAN DISTRICT, SEMARANG REGENCY, CENTRAL JAVA PROVINCE, INDONESIA (NUMBER OF CATTLES, COST OF PRODUCTION, QUALITY OF MILK) AT THE FARMER LEVEL - Lepo, Ian Aine; Setiadi, Agus; Sudjadmogo, Sudjadmogo (Animal Agriculture Journal, 2013)
This research was done in(October-September) 2012 at Kopeng and Tekelang village, District of Getasan. The method used in this research was survey which interviews to 60 farmers. Questionnaiers are in Appendics I. The studys primary objective was to examine the factors {No. Of cattle (X1), cost of feed (X2), Quality of Milk (X3)} that affects over the price of the milk (Y). The (independent) variables observed had significant effects over the (dependent) price of the milk. The research results have indicated that the constant (milk price) 65.863 sig. P ≤ 0.000 (99.99%). Which gives the linear equation Y = 3.082 + 0.042 (X1) – 2.9E10 (X2) + 0.003 (X3). The feed cost almost exceeds the income for some of the farmers. It did affects the price of the milk by increasing also the milk price. Analysis tools used in this study is quantitative discriptive (Multiple Linear Regression) with F-test (F=9.843 p ≤ 0.0001) R Square (R2) = 0.345 p ≤ 0.05), t-Test (X1 = 2.469 p ≤ 0.05, X2 = 2.797 p ≤ 0.05, X3 = 4.268 P ≤ 0.05. The model of the study is being matched 35 % for the price of the milk but 65 % depends on other factors, such as education, farmers strength, motivational attitude, labor force, time figured, level of education, farmers age, animal hausbandry management practices, and government policies et. cetera. The study explored also the role of cooperativism in dairy cattle farming in those Getasan villages (Kopeng and Tekelang),Semarang Regency, Central Java Province.. There were significant relationships among sharing of knowledge and information, sharing of resources, and participation in decision making and milk production in Getasan Village. Interestingly noted that the milk is paid for on the basis of compositional and hygienic quality, assessed according to the fat, protein, lactose, total bacterial count (TBC), somatic cell count (SCC) content of milk. Improving milk compositonal quality will generate additional income. Under tropical conditions the lactating animals maintain higher body condition which results in lower feed intake and milk yield. In nutshell, the suggestion for milk of desirable composition may be produced for special purposes through selection of appropriate physiological states coupled with special feed ingredients, in the dairy production system.Key words: multiple linear regression, dairy cooporatives, husbandry management